Food consumption and COVID-19 risk perception of university students (2022)
The aim of this study is to examine the differences in COVID-19 risk perception of university students, depending on their food consumption (proinflammatory diet and non-proinflammatory diet). A total of 513 university students aged between 16 and 42 years (PDG: mean 20.26, standard deviation 3.07; NPDG: mean 21.78, standard deviation 4.12) were interviewed via an online questionnaire. The study subjects were divided into two groups: a proinflammatory diet group (PDG) who obtained higher values on pasta, rice, bread, pastries, juices, and fruit consumption; and non-proinflammatory diet group (NPGD) who presented low consumption on these products. Significant results were obtained (p < 0.05) on how a proinflammatory diet presented a higher COVID-19 risk perception in university students (PDG 7.92 ± 2.46; NPGD 7.12 ± 2.28). In addition, students with a proinflammatory diet presented lower values in depression (PDG 48.32 ± 5.33; NPGD 49.83 ± 5.23) and loneliness (PDG 4.91 ± 1.67; NPGD 5.14 ± 1.68) and higher values in openness to experience (PDG 7.5 ± 1.53; NPGD 7.20 ± 1.54) than students with a non-proinflammatory diet. Furthermore, students with a proinflammatory diet were most affected in work (loss of work, reduced work, or unaffected work) due to the COVID-19 crisis (PDG 2.54 ± 0.65; NPGD 3.99 ± 0.26). The proinflammatory diet group presented higher values in complying with the confinement rules than students with a non-proinflammatory diet (PDG 8.26 ± 1.83; NPGD 7.74 ± 2.10). The results of this study may be a useful tool to explain and prevent both the psychological and general health consequences of the COVID-19 pandemic in students.